MAPPING INDONESIA'S READINESS FOR ASEAN ENERGY MARKET INTEGRATION (AEMI): ANALYSIS OF POLICY HARMONIZATION AND INFRASTRUCTURE DEVELOPMENT IN THE ELECTRICITY SECTOR - Silvia Dian Anggraeni; Novita P. Rudiany; Ardila Putri; Naeli Fitria; Hardhana Dinaring Danastri; Tiara Amima Putri (Bajang Institute, 2025)
As a form of commitment to realizing inclusive access to modern energy and reducing greenhouse gas emissions to achieve sustainable development goals as stated in the Paris Agreement, the Association of Southeast Asian Nations (ASEAN) has designed and implemented various energy cooperation programs at the regional level. Through the ASEAN Plan of Action on Energy Cooperation (APAEC), the ASEAN countries emphasize the regional interconnectivity agenda through infrastructure development projects, one of which is the ASEAN Power Grid (APG). However, there are still several obstacles in the implementation of cooperation under the APAEC framework, namely the absence of a coherent institutional and regulatory framework, as well as differences in tariff, taxes, and energy pricing policies among ASEAN member countries. ASEAN Energy Market Integration (AEMI) is a recommended scheme for strengthening and deepening the established regional energy cooperation under the APAEC framework. This study attempts to analyze Indonesia's readiness to face the discourse on the formation of AEMI, particularly in the electrical energy sector, by using two indicators, namely the harmonization of policies and regulations, and infrastructure development. Using qualitative methods and semi-structured in-depth interview techniques, this study seeks to explore whether the regulations enacted by the Government of Indonesia comply with regional agreements, and to what extent the Government of Indonesia has committed to regional infrastructure development. This study concludes that Indonesia has made efforts to harmonize policies and established agreements on the APG framework with other ASEAN countries. However, Indonesia still needs to map its perception of the need for energy comprehensively and look for the right form of coordination among related institutions to gain more advantages in the ASEAN energy market integration.